Vaccination of Children with Chronic Kidney Disease - MP. . Ustinov; A. A. Tarasova (Эпидемиология и вакцинопрофилактика)
Recommendations highlighted features vaccination of children with rheumatic diseases. It is shown how the immunization scheme may be changed according to the pathology and the age of the child.